Acid-Induced Inflammatory Cytokines in Osteoblasts: A Guided Path to Osteolysis in Bone Metastasis - Di Pompo, Gemma; Errani, Costantino; Gillies, Robert; Mercatali, Laura; Ibrahim, Toni; Tamanti, Jacopo; Baldini, Nicola; Avnet, Sofia (Frontiers in Cell and Developmental Biology, 2021)
Bone metastasis (BM) is a dismal complication of cancer that frequently occurs in patients with advanced carcinomas and that often manifests as an osteolytic lesion. In bone, tumour cells promote an imbalance in bone remodelling via the release of growth factors that, directly or indirectly, stimulate osteoclast resorption activity. However, carcinoma cells are also characterized by an altered metabolism responsible for a decrease of extracellular pH, which, in turn, directly intensifies osteoclast bone erosion. Here, we speculated that tumour-derived acidosis causes the osteoblast-osteoclast uncoupling in BM by modulating the pro-osteoclastogenic phenotype of osteoblasts. According to our results, a low pH recruits osteoclast precursors and promotes their differentiation through the secretome of acid-stressed osteoblasts that includes pro-osteoclastogenic factors and inflammatory mediators, such as RANKL, M-CSF, TNF, IL-6, and, above the others, IL-8. The treatment with the anti-IL-6R antibody Tocilizumab or with an anti-IL-8 antibody reverted this effect. Finally, in a series of BM patients, circulating levels of the osteolytic marker TRACP5b significant correlated with IL-8. Our findings brought out that tumour-derived acidosis promotes excessive osteolysis at least in part by inducing an inflammatory phenotype in osteoblasts and these results strengthen the use of anti-IL-6 or anti-IL-8 strategies to treat osteolysis in BM.